Ductility Enhancement of Post-Northridge Connections by Multilongitudinal Voids in the Beam Web - Naimi, Sepanta; Çelikağ, Mürüde; Hedayat, Amir A. (Hindawi Publishing Corporation, 2013)
Since the earthquakes in Northridge and Kobe in 1994 and 1995, respectively, many investigations have been carried out towards improving the strength and ductility of steel beam to column pre- and post-Northridge connections. In order to achieve these objectives, recent researches are mainly focused on three principles: reducing the beam section to improve the beam ductility, adding different kinds of slit damper to beam and column flanges to absorb and dissipate the input earthquake energy in the connection and strengthening the connection area using additional elements such as rib plates, cover plates, and flange plates to keep the plastic hinges away from the column face. This paper presents a reduced beam section approach via the introduction of multilongitudinal voids (MLV) in the beam web for various beam depths varying from 450 mm to 912 mm. ANSYS finite element program was used to simulate the three different sizes of SAC sections: SAC3, SAC5, and SAC7. Results showed an improvement in the connection ductility since the input energy was dissipated uniformly along the beam length and the total rotation of the connection was over four percent radian.
The file in this item is the publisher version (published version) of the article.
Keywords: DESIGN, EARTHQUAKE, LESSONS; STEEL MOMENT CONNECTIONS, DETAILS, MULTIDISCIPLINARY SCIENCES; STRENGTH, Q1-390, Science (General)